Cognitive and human factors in legal layperson decision making: Sources of bias in juror decision making. (July 2022) - Curley, Lee J.; Munro, James; Dror, Itiel E.
Juries in adversarial courts are tasked with several responsibilities. They are asked to: 1) assess the credibility and reliability of the evidence presented; 2) deliberate; 3) and then reach a decision. Jurors are expected to evaluate said evidence in a rational/impartial manner, thus allowing the defendant their right to a fair trial. However, psychological research has shown that jurors are not rational and can reach inaccurate decisions by being biased by certain factors. The aim of the current review was to explore the potential sources from which biases are introduced into the jury. Three main sources of bias were focussed upon: 1) pre-trial bias; 2) cognitive bias; 3) bias from external legal actors (expert witnesses). Legal scholars commonly cite deliberations as a method of attenuating individual juror bias, this claim is evaluated in the review. The review concludes that bias is a multifaceted phenomenon introduced from many different elements, and that several sources of bias may interact with one another during a jury trial to cause the effects of bias to snowball. Four recommendations are made: 1) juror selection should be utilised to create heterogenous juries that challenge problematic biases from individual jurors; 2) increase the quality of expert testimony through training; 3) procedures such as Linear Sequential Unmasking should be adopted by expert witnesses to filter out some sources of bias; 4) legal professionals and jurors should be educated about the effects that biases may have on decision making; 5) more research into bias in jurors is needed.